2022
DOI: 10.3390/ijms232214262
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of the NPF Genes in Cotton

Abstract: The NPF (NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY) transports various substrates, including nitrogen (N), which is essential for plant growth and development. Although many NPF homologs have been identified in various plants, limited studies on these proteins have been reported in cotton. This study identified 75, 71, and 150 NPF genes in Gossypium arboreum, G. raimondii, and G. hirsutum, respectively, via genome-wide analyses. The phylogenetic tree indicated that cotton NPF genes are subdivided into e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The distribution of CsNPFs in different subfamilies is as follows: NPF1 (4), NPF2 (8), NPF3 (2), NPF4 (8), NPF5 (17), NPF6 (6), NPF7 (6), and NPF8 (3). Among them, NPF1 is more closely related to the NPF2 subfamily on one branch, NPF4 is more closely related to NPF6, and NPF7 is more closely related to NPF8, which is consistent with the results of previous research [ 8 , 10 , 11 , 38 , 39 ]. To distinguish the subfamilies of NPF genes, we renamed all CsNPF genes according to the international nomenclature, based on their homology with AtNPF genes ( Table S1 ) [ 40 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of CsNPFs in different subfamilies is as follows: NPF1 (4), NPF2 (8), NPF3 (2), NPF4 (8), NPF5 (17), NPF6 (6), NPF7 (6), and NPF8 (3). Among them, NPF1 is more closely related to the NPF2 subfamily on one branch, NPF4 is more closely related to NPF6, and NPF7 is more closely related to NPF8, which is consistent with the results of previous research [ 8 , 10 , 11 , 38 , 39 ]. To distinguish the subfamilies of NPF genes, we renamed all CsNPF genes according to the international nomenclature, based on their homology with AtNPF genes ( Table S1 ) [ 40 ].…”
Section: Resultssupporting
confidence: 91%
“…There are two classification systems for the NPF gene family, as follows: one system is based on a phylogenetic analysis of 1077 sequences from 22 plant genomes and 24 nonplant sequences, dividing the family into 10 supergroups and 32 groups [ 45 ]; and the other system divides the NRT1/PTR family into eight subfamilies (NPF1-NPF8), based on an analysis of 2398 sequences from 33 full-sequence genomes [ 40 ]. Previous studies have generally conformed to the criteria of the latter division [ 8 , 11 , 38 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Recently, a new classification method appeared in Brassica napus .…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptome and genome‐wide studies reported the expression of 47 GhNPF in all tissues in cotton plants and suggested that GhNPF6.11, −7.1 and −8.1 could be redundant in some tissues (Dong et al, 2022). GhNPF4.8, −6.10, −6.14, −7.8 , −7.10 and −7.13 are highly expressed in roots and could regulate root uptake and xylem loading, while GhNPF4.8 and GhNPF6.18 were speculated to regulate phloem loading and intracellular transport due to their high expression in the stem and leaf (Dong et al, 2022). Nitrogen starvation induces the expression of some GhNPF genes.…”
Section: Regulation Of N Allocation To Vegetative and Reproductive Br...mentioning
confidence: 99%
“…Similarly, N‐starvation induces the high expression of GhNPF6.5 , − 6.7 , – 6.9 and – 7.8 in the shoots, whereas GhNPF2.12 , – 6.13 and – 6.17 are repressed. Though VIGS‐mediated silencing of GhNPF6.14 exhibited no difference in root biomass compared to the wildtype, the shoot of ghnpf6.14 ‐mutant accumulated less N, suggesting that GhNPF6.14 could be an essential regulator of vegetative growth in cotton (Dong et al, 2022).…”
Section: Regulation Of N Allocation To Vegetative and Reproductive Br...mentioning
confidence: 99%
“…These findings suggest that plant growth and productivity under stress conditions can be best achieved by improving N use efficiency. In addition, the GhNPF6.14 gene affects growth and nitrogen uptake and accumulation of cotton ( Dong et al., 2022 ). Nevertheless, the NPF gene family has been poorly characterized in abiotic stress response of cotton.…”
Section: Introductionmentioning
confidence: 99%